1990
DOI: 10.1590/s0074-02761990000100007
|View full text |Cite
|
Sign up to set email alerts
|

Human leptospirosis in a slum area in the city of Rio de Janeiro, Brazil: a serological and epidemiological study

Abstract: A serologic survey was carried out on slum dwellers in the city of Rio de Janeiro. A total of 259 serum samples from male and female individuals of different age groups were tested for the presence of antileptospire antibodies by microagglutination. Prevalence data were analyzed in relation to the major risk factors present at the site, mainly represented by the presence of carrier animals and the occurrence of frequent floods. Of the samples tested, 25% reacted with antigens of different serogroups at titres … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1
2

Year Published

1992
1992
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 0 publications
0
5
1
2
Order By: Relevance
“…However, individual and ecological analysis showed that Leptospira sp was inversely associated with education level. The seroprevalence (12.4%) observed in Salvador was lower than what has been reported from other regions of Brazil 24 and other developing countries 19 , where it ranged from 25.0 to 54.2%. It should be noted, however, that the highest levels have been reported among selected populations living in high-risk areas where leptospirosis is hyperendemic or where there is a high degree of exposure.…”
Section: Discussioncontrasting
confidence: 67%
“…However, individual and ecological analysis showed that Leptospira sp was inversely associated with education level. The seroprevalence (12.4%) observed in Salvador was lower than what has been reported from other regions of Brazil 24 and other developing countries 19 , where it ranged from 25.0 to 54.2%. It should be noted, however, that the highest levels have been reported among selected populations living in high-risk areas where leptospirosis is hyperendemic or where there is a high degree of exposure.…”
Section: Discussioncontrasting
confidence: 67%
“…Serological evidence of exposure to Leptospira spp. in Brazil [80][83] shows a moderately higher risk among males: a random-effects meta-analysis of four surveys ( N  = 3996 subjects) yielded an OR of 1.41 (95%CI 1.18–1.69) (Figure 4). …”
Section: Resultsmentioning
confidence: 99%
“…In this sense, slums can be considered endemic areas for leptospirosis, yet displaying low incidence rates during the outbreak. A survey performed in one of the lowland Rio de Janeiro slums demonstrated a human serological prevalence as high as 25 %, with an infection rate of 1% per year (Pereira & Andrade, 1990). In such cases, infection is found to be related to occupational and behavioral factors, presenting a typically endemic evolutionary pattern (Velazquez et al, 1984).…”
Section: Resultsmentioning
confidence: 99%